Mining RNA-Seq Data to Depict How Penicillium digitatum Shapes Its Transcriptome in Response to Nanoemulsion - Yang, Ruopeng; Chen, Xiu; Huang, Qiang; Chen, Chuying; Rengasamy, Kannan R. R.; Chen, Jinyin; Wan, Chunpeng (Craig) (Frontiers in Nutrition, 2021)
Penicillium digitatum is the most severe pathogen that infects citrus fruits during storage. It can cause fruit rot and bring significant economic losses. The continuous use of fungicides has resulted in the emergence of drug-resistant strains. Consequently, there is a need to develop naturally and efficiently antifungal fungicides. Natural antimicrobial agents such as clove oil, cinnamon oil, and thyme oil can be extracted from different plant parts. They exhibited broad-spectrum antimicrobial properties and have great potential in the food industry. Here we exploit a novel cinnamaldehyde (CA), eugenol (EUG), or carvacrol (CAR) combination antifungal therapy and formulate it into nanoemulsion form to overcome essential oil’s lower solubility and instability. In this study, the antifungal activity evaluation and transcriptional profile of Penicillium digitatum exposed to compound nanoemulsion were evaluated. Results showed that compound nanoemulsion had a striking inhibitory effect on P. digitatum in a dose-dependent manner. According to RNA-seq analysis, 2169 differentially expressed genes, including 1028 down-regulated and 1141 up-regulated genes between control and nanoemulsion treated samples. GO analysis indicated that the differentially expressed genes were mainly involved in intracellular organelle part of cell component; cellular respiration, proton transmembrane transport of biological process and guanyl nucleotide-binding molecular function. KEGG analysis revealed that metabolic pathway, biosynthesis of secondary metabolites and glyoxylate and dicarboxylate metabolism were the most highly enriched pathways for these differentially expressed genes. Taken together, we can conclude that the promising antifungal activity of nanoemulsion with multiple action sites against P. digitatum. These outcomes would deepen our knowledge of the inhibitory mechanism from molecular aspects and exploit naturally, efficiently and harmlessly antifungal agents in the citrus postharvest industry.